Food Insecurity and Scarcity in Pakistan: Causes and Impacts - Fatima, Mahum (Annals of Human and Social Sciences, 2024)
The objective of this paper is to highlight the issue of food insecurity in Pakistan along with the causes and impacts of this crisis in recent years. The background of the concept of national security is extremely important and food scarcity has been on the rise in the past few years in Pakistan; its causes ranging from the exacerbating climatic conditions to inefficient management of resources and production. There is a dire need to tackle this issue in order to prevent the rising numbers of poverty and starvation from escalating further. The metholodgy includes using secondary sources such as journal articles, books, research papers etc to analyse and summarize the issue of food insecurity in Pakistan in recent years. The results of this research paper indicate that the food shortage has reached unprecedented levels with the recent flooding and climate change. The recommendations summarized at the end of this research paper is that the government of Pakistan needs to take immediate steps to install sustainable food policies that will counter the rising scarcity.